The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10514-017-9677-2
|View full text |Cite
|
Sign up to set email alerts
|

Progress and prospects of the human–robot collaboration

Abstract: Recent technological advances in hardware design of the robotic platforms enabled the implementation of various control modalities for improved interactions with humans and unstructured environments. An important application area for the integration of robots with such advanced interaction capabilities is human-robot collaboration. This aspect represents high socio-economic impacts and maintains the sense of purpose of the involved people, as the robots do not completely replace the humans from the work proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
318
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 526 publications
(322 citation statements)
references
References 175 publications
0
318
0
4
Order By: Relevance
“…we can conclude that the algorithm (7) ensures the speed of achieving the control goal (5) of order 3 1 k . Achieving the control goal also occurs with non-uniqueness j j q min .…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…we can conclude that the algorithm (7) ensures the speed of achieving the control goal (5) of order 3 1 k . Achieving the control goal also occurs with non-uniqueness j j q min .…”
mentioning
confidence: 80%
“…However, a significant part of the problems -such as performance improvement, invariance to external influences, changes in the characteristics of the control object, etc., are not effectively solved by this approach. Therefore, an urgent need has arisen for improving management systems using non-traditional management technologies [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work has addressed the sensing and collaborative strategies [13], [14], but both works focused on the safety interaction between human and robots in an industrial setting. Furthermore, Ajoudani et al work reported the control strategies, interaction modalities and collaborative interfaces for pHRC [15]. Although, these scholars made efforts to present an up-to-date overview on HRC, but to the best of the authors' knowledge, none of them covered exhaustively the most relevant challenges due to the fast-growing trends in the pHRC technologies and the tremendous demands in the applicability of robotic systems in our day-to-day activities.…”
Section: Introductionmentioning
confidence: 99%
“…These applications have driven research in many fundamental topics, such as adaptative role allocation during collaboration [9], control of contacts and physical interaction [10], learning by demonstration [11], safe control [12]. Specifically, safety issues have received a great deal of attention, both in research and in standardization [13], [12], [14], [15].…”
Section: Introductionmentioning
confidence: 99%